Intragenomic rDNA variation - the product of concerted evolution, mutation, or something in between? - Wang, Wencai; Zhang, Xianzhi; Garcia, Sònia; Leitch, Andrew R; Kovařík, Aleš (Heredity, 2023)
The classical model of concerted evolution states that hundreds to thousands of ribosomal DNA (rDNA) units undergo homogenization, making the multiple copies of the individual units more uniform across the genome than would be expected given mutation frequencies and gene redundancy. While the universality of this over 50-year-old model has been confirmed in a range of organisms, advanced high throughput sequencing techniques have also revealed that rDNA homogenization in many organisms is partial and, in rare cases, even apparently failing. The potential underpinning processes leading to unexpected intragenomic variation have been discussed in a number of studies, but a comprehensive understanding remains to be determined. In this work, we summarize information on variation or polymorphisms in rDNAs across a wide range of taxa amongst animals, fungi, plants, and protists. We discuss the definition and description of concerted evolution and describe whether incomplete concerted evolution of rDNAs predominantly affects coding or non-coding regions of rDNA units and if it leads to the formation of pseudogenes or not. We also discuss the factors contributing to rDNA variation, such as interspecific hybridization, meiotic cycles, rDNA expression status, genome size, and the activity of effector genes involved in genetic recombination, epigenetic modifications, and DNA editing. Finally, we argue that a combination of approaches is needed to target genetic and epigenetic phenomena influencing incomplete concerted evolution, to give a comprehensive understanding of the evolution and functional consequences of intragenomic variation in rDNA.
Keywords: mutace; Animals; Genetic Variation; Phylogeny; Fungi; ribozomální DNA; zvířata; DNA, Ribosomal; fylogeneze; genetická variace; Polymorphism, Genetic; houby; Mutation; Evolution, Molecular; molekulární evoluce; polymorfismus genetický